An Intensified Esterification Process of Palm Oil Fatty Acid Distillate Catalyzed by Delipidated Rice Bran Lipase ... : عملية استرة مكثفة لنواتج تقطير حمض النخيل الدهني التي يحفزها ليباز نخالة الأرز المشحوم ... - Fui Chin Chong; Beng Ti Tey; Zanariah Mohd Dom; Nordin Ibrahim; Raja Noor Zaliha Raja Abdul Rahman; Tau Chuan Ling (OpenAlex, 2006)
An intensified esterification process was operated by circulating 10 l of reaction mixtures, consisting of palm oil fatty acid distillate (PFAD) and glycerol in hexane, through a packed-bed reactor (PBR) filled with 10 kg of delipidated rice bran lipase (RBL). The influence of the process parameters, such as reaction temperature and type of water-removal agent, on the performance of this intensified esterification process were investigated. The highest degree of esterification (61%) was achieved at a reaction temperature of 65 masculineC, using silica gels as the water-removal agent. Thin-layer chromatography (TLC) analysis showed that the major composition of the esterified product was diacylglycerol. ... : تم تشغيل عملية الأسترة المكثفة عن طريق تدوير 10 لتر من مخاليط التفاعل، التي تتكون من نواتج تقطير حمض زيت النخيل الدهني (Pfad) والجلسرين في الهكسان، من خلال مفاعل سريري معبأ (PBR) مملوء بـ 10 كجم من ليباز نخالة الأرز (RBL). تم التحقيق في تأثير معلمات العملية، مثل درجة حرارة التفاعل ونوع عامل إزالة الماء، على أداء عملية الأسترة المكثفة هذه. تم تحقيق أعلى درجة من الأسترة (61 ٪) عند درجة حرارة تفاعل تبلغ 65 درجة مئوية، باستخدام هلام السيليكا كعامل لإزالة الماء. أظهر تحليل كروماتوغرافيا الطبقة الرقيقة (TLC) أن التركيب الرئيسي للمنتج المؤستر كان ثنائي أسيل جليسرول. ...